2023
DOI: 10.1155/2023/4813225
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of New Delhi Metallo-β-Lactamase (NDM) Genes Detected from Clinical Strains of Escherichia coli Isolated in Ouagadougou, Burkina Faso

Abstract: The emergence and spread of carbapenem resistance in Gram-negative bacilli such as Klebsiella pneumoniae, Escherichia coli, Acinetobacter baumannii, and Pseudomonas aeruginosa through the production of carbapenemases is a global phenomenon. It threatens patient care and leads to therapeutic impasses. This study aims to genotypically determine the prevalence of the most frequent carbapenemase genes among multidrug-resistant E. coli strains isolated from patients at a biomedical analysis laboratory. A total of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Thus, eventual presence of GES-2 variant, exhibiting an increased hydrolysis of carbapenems (Poirel et al, 2001), in our bacterial strains, might justified carbapenem resistance of IMP gene-negative isolates. Interestingly, the encoding-carbapenemase genes, such as blaNDM, blaVIM and bla KPC were found in GNB clinical isolates as previously reported in other studies in this country (Dembele et al, 2021;Kabore et al, 2023;Ouattara et al, 2023;Bambara et al, 2023). These carbapenem resistance genes not researched in this study could also explained the finding.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Thus, eventual presence of GES-2 variant, exhibiting an increased hydrolysis of carbapenems (Poirel et al, 2001), in our bacterial strains, might justified carbapenem resistance of IMP gene-negative isolates. Interestingly, the encoding-carbapenemase genes, such as blaNDM, blaVIM and bla KPC were found in GNB clinical isolates as previously reported in other studies in this country (Dembele et al, 2021;Kabore et al, 2023;Ouattara et al, 2023;Bambara et al, 2023). These carbapenem resistance genes not researched in this study could also explained the finding.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, carbapenem resistance profile was carried out by an automated method (Hu et al, 2019) which improve resistance detection. Whereas, in this study phenotypic detection of carbapenem-resistant strains has been performed using manual disk diffusion method (EUCAST/CASFM, 2022), by which it is difficult to demonstrate carbapenem resistance (Kabore et al, 2023). All bacterial isolates resistant to carbapenem and/or to aztreonam therefore suspicious of carbapenemase production were screening by molecular approaches to detect IMP gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ESBL genes that are often located on plasmids are particularly concerned by this phenomenon that favours their dissemination [ 26 ]. Several studies reported ESBL Enterobacterales in Burkina Faso from clinical samples [ 27 , 28 , 29 , 30 ] and in wastewater and salads [ 31 ]. In this study, we analysed ESBL-producing E. coli (ESBL- Ec ) and K. pneumoniae (ESBL- Kp ) from environmental samples from Ouagadougou, capital city of Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%
“…One study conducted in a referral teaching hospital identified 17 carbapenemase-producing strains, 4 in clinical samples and 13 in fecal carriage isolates from 443 Gram-negative bacteria [19]. Another study reported NDM genes in clinical E. coli isolates [22]. Recent studies in the country have discovered that carbapenemase-producing bacteria or their related genes are prevalent in the hospital waste water, implying their likely presence in clinical samples as well [23,24].…”
Section: Introductionmentioning
confidence: 99%